Determination of Thermal Conductivity of Ambon Banana (Musa Paradisiaca L.) in One Dimensional Heat Transfer Mechanism - Argo, Bambang Dwi; Komar, Nur; Damayanti, Retno (Fakultas Teknologi Pertanian Universitas Brawijaya, 2000)
The knowledge of thermal conductivity (k) is very important to estimate the flux ofheat transfer on material. The thermal conductivity Ambon Banana fruit (Musaparadiciaca L.) has been exploited in our works and the results are important forconstructing a system of food manufacture process such as heating, cooling, drying etc. The aims of this experiment are; 1) to determine the thermal conductivity of Ambonbanana fruit, 2) to know an influence of temperature gradient on the thermal conductivity. The configuration of experiment are fixed and they are; 1) the heat transfer in onedimensional, 2) the initial and boundary condition in certain value, 3) materialconsidered homogeny, and 4) experiment in unsteady state condition The thermal conductivity is calculated by the numerical method (Method of CrankNicholson). The Ambon banana fruit is milled to obtain the homogenize of size and physical characteristic material. The given temperature treatment is of 40°C and of 70°C. We obtain that the mean of thermal conductivity of Ambon banana fruit at temperature of 40°C is (0.525±0.031) W/m°C and of 70°C is (0.530±0.066) W/m°C. Wecan make a conclusion that the higher of gradient temperature, affect thermal diffusivity.Keywords : thermal conductivity, heat transfer, unsteady state, one dimensional.